2017
DOI: 10.21767/1791-809x.1000478
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of Antibiotic Therapy among University Community in South Jordan

Abstract: Misuse of antibiotic is a common problem worldwide; of the common features of this problem were failure to complete the course of treatment, skipping doses, reusing leftover antibiotics, or self-treatment with antibiotics. This indeed can have a negative impact on individuals and community on both economic and health levels. It was established that misusing antibiotics might be a major determinant in the development of bacterial resistance, which became a major global public health problem. In Jordan, antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This reason was not a prevalent factor in some studies. 24 , 25 However, other studies claimed that lack of time and previous experience with similar symptoms are influential factors promoting self-medication. 5 , 26 Moreover, lack of time intermingles with the urgency of use.…”
Section: Discussionmentioning
confidence: 99%
“…This reason was not a prevalent factor in some studies. 24 , 25 However, other studies claimed that lack of time and previous experience with similar symptoms are influential factors promoting self-medication. 5 , 26 Moreover, lack of time intermingles with the urgency of use.…”
Section: Discussionmentioning
confidence: 99%
“…37 Studies from developing nations like China mainly reported convenience and cost saving, and South Jordan reported previous positive experience with the antibiotics and difficulty reaching physician especially for low-income population as prevalent factors in the practice of self-medication among consumers. 38,39 Our study also identified the lack of comprehensive knowledge and poor understanding of antibiotics among consumers. Consumers are unaware of correct usage and proper administration of antibiotics, rather they have misapprehensions about antibiotics.…”
Section: Discussionmentioning
confidence: 84%
“… 37 Studies from developing nations like China mainly reported convenience and cost saving, and South Jordan reported previous positive experience with the antibiotics and difficulty reaching physician especially for low-income population as prevalent factors in the practice of self-medication among consumers. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…although with a smaller per cent than students in Nepal (98.2 per cent) (Shrestha, 2019: 76), but larger than in South Jordan (67.2 per cent) (Nawafleh et al, 2017). Nevertheless, as 23.9 per cent identified that antibiotics could kill viruses too, there is room for improvement.…”
Section: Knowledgementioning
confidence: 99%